Demographic, Clinical and Hematological Parameters of Patients with Severe and Non Severe Dengue Infection - Samiullah Khan, Mohsin Ul Alam, Naseeburahman, Radhia Khan, Tariq Mehar, Muhammad Nadeem (Pakistan Journal of Medical & Health Sciences, 2023)
Background: There has been a remarkable rise in the worldwide frequency of dengue in recent decades owing to the ineffectiveness of existing management methods including vaccinations and pesticides. Objective: To assess the demographic, clinical and hematological parameters of patients infected with severe and non severe dengue Methodology: This cross sectional study was carried out at the Medicine department, Khalifa Gul Nawaz Teaching Hospital, Bannu Medical College Bannu from May 2022 to October 2022. All the data like demographic, clinical and data related to hematological parameters was recorded on pre-designed Performa. The data was analyzed using SPSS 23. Results: In the current study, totally 180 patients were enrolled. The patients were categorized into NSDI and SD1 group. There were 96 (67.8%) males and 46 (32.4%) females’ patients in NSDI group while there were 28 (73.7%) males and 10 (26.3%) females in SD1 group. Fever was observed in 138 (97.2%) patients in NSDI group and 38 (100%) patients in SDI group. Platelet transfusion was needed in 55 (38.7%) patients in NSDI group while it was needed in 26 (68.4%) patients in SDI group. The mean ±SD Platelet Count x 103mm3 was 39 ±52.5 in NSDI group and 31.5±67.6 in SDI group. The mean ±SD Lowest Platelet Count x 103 mm3 was 28±42 and 21.5± 17 in NSDI group and SDI group respectively. The mean ±SD HCT % was 40.8± 6.7 in NSDI group and 36.0± 12.1 in SDI group. The mean ±SD Leukocytes Count x 103 mm3 was 4400±5425 and 8050±9350 in NSDI group and SDI group respectively. Conclusion: The key to treating and predicting dengue as severe and non-severe cases is to be aware of clinical aspects as well as test results such hematological parameters. Keywords: Demographic, clinical and hematological parameters, severe and non severe dengue infection